2016
DOI: 10.1159/000446978
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis with High Cut-Off Hemodialyzers in Patients with Multi-Drug Resistant Gram-Negative Sepsis and Acute Kidney Injury: A Retrospective, Case-Control Study

Abstract: Background: Hemodialysis with high cut-off continuous veno-venous hemodialyzer (HCO-CVVHD) removes mediators of organ dysfunction during sepsis. This study assessed the clinical effects of HCO-CVVHD as compared to high-flux (HF) membranes during gram-negative sepsis. Methods: Intensive care unit (ICU), septic patients treated with HCO-CVVHD or HF-CVVHDF for AKI were retrospectively observed (January 2013-December 2014). Mechanical ventilation, vasopressors' requirements, ICU length of stay (LOS) and ICU in-hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
(38 reference statements)
0
25
0
1
Order By: Relevance
“…A small study by Morgera et al showed a reduction in serum‐levels of proinflammatory cytokines in septic patients and a reduced need for catecholamines . A retrospective analysis in sepsis patients showed a reduced need for vasoactive drugs and mechanical ventilation as well as improved short‐term survival . However, none of the studies thoroughly investigated prospectively the filter characteristics in detail and for the whole treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…A small study by Morgera et al showed a reduction in serum‐levels of proinflammatory cytokines in septic patients and a reduced need for catecholamines . A retrospective analysis in sepsis patients showed a reduced need for vasoactive drugs and mechanical ventilation as well as improved short‐term survival . However, none of the studies thoroughly investigated prospectively the filter characteristics in detail and for the whole treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…However, these membranes are currently used with diffusive methods or after optimization of their architecture to limit albumin losses while preserving their capacity to remove middle molecular weight molecules [35,36]. Observational studies including patients with septic shock treated with high cutoff membranes and diffusive CRRT found an effective removal of cytokines and a reduction of intensive care unit length of stay and mortality [37][38][39].…”
Section: Removing Cytokinesmentioning
confidence: 99%
“…Overall, the studies are suggestive of a decrease in inflammatory cytokines and improvement of hemodynamics, along with an improvement in ICU patient severity of illness scores as reported by Morgera et al [ 27 30 ]. One study comparing continuous veno-venous hemodialysis with HCO membranes (HCO-CVVHD; at a dose of 35 ml/kg/h) vs CVVHDF (at a dose of 45 ml/kg/h) showed an ICU mortality benefit (37.5 and 87.5% for HCO-CVVHD and CVVHDF groups, respectively ( p = 0.03)), but no significant difference was found in ICU-LOS and in-hospital mortality [ 32 ]. Furthermore, the High Cut-Off Sepsis study (HICOSS) comparing conventional and HCO membranes was stopped prematurely after enrolment of 81 patients due to a lack of 28-day mortality benefit (HCO (31%) vs conventional (33%)) and lack of a difference in vasopressor requirement or ICU-LOS [ 35 ].…”
Section: Introductionmentioning
confidence: 99%